RehabilitacjaSupervision of rehabilitation training in patients after cardiac surgery – physiotherapist tasks - Przywarska, Izabela; Dylewicz, Piotr; Bromboszcz, Janusz; Borowicz-Bieńkowska, Sławomira; Wilk, Małgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
The physiotherapeutic management of patients rehabilitated after cardiac surgery should take into account the current specificity of patient’s selection - increasing number of patients of medium and high risks. Especially these groups of patients need to have a stricter supervision during physical exercises. Extended supervision over a patient allows for the use of exercises that enable to attain the best effects at the minimized level of risk of developing complications. Although one should keep in mind that safety of the training depends not only on the course of exercises and on the patient’s health state but also on the specialized knowledge on disease prevention, possibilities of giving instant medical aid, but in the case of home rehabilitation it also depends on family education. Responsibility for the supervision of patient relies on physiotherapist - conducting directly physical exercise while physician overseeing treatment and rehabilitation is responsible for the whole rehabilitation process.